Parallel fragments : Measuring their impact on translation performance. (May 2017) - Abdul-Rauf, Sadaf; Schwenk, Holger; Nawaz, Mohammad
Highlights: Phrase fragments have proved to be a valuable resource for increasing translation and natural language generation performance. A novel approach to find parallel fragments from comparable corpora is presented which is simple and efficient in processing. Difference in translation improvement for fragments extracted from related versus non related corpus is presented. Comparison of impact of parallel fragments vs. sentences is reported highlighting the significance of parallel segments. Proposed approach is compared theoretically with an earlier approach on all phases of the fragment extraction pipeline. Abstract: Lack of parallel corpora have diverted the direction of research towards exploring other arenas to fill in the dearth. Comparable corpora have proved to be a valuable resource in this regard. Interestingly other than the parallel sentences extracted from comparable corpora, parallel phrase fragments have also proved to be beneficial for statistical machine translation. We present a novel approach based on an efficient framework for parallel fragment extraction from comparable corpora. Using the fragments as additional corpus for translation, we are able to obtain an improvement of 0.88 and 0.89 BLEU points on test data for Arabic–English and French–English systems respectively. We have also conducted a detailed analysis of impact of fragments extracted from related vs non-related corpus. A comparison of impact of parallel fragments vs. parallel sentences is also presented highlighting the significance of parallel segments for statistical machine translation. The article concludes with a crude comparative analysis of our approach with an existing fragment extraction technique at various stages of the fragment extraction pipeline.